Theoretical Background of Input-Output Analysis and its Application in Albania - Skender Uku; Elona Shehu (European Scientific Journal, ESJ, 2024)
The input-output (IO) method is widely used in economic analysis to understand the relationship between sectors of the economy. One of the major advantages of the IO method is its ability to capture the direct and indirect effects of different policies in one sector on other sectors of the economy. The IO table system is a crucial component of the European System of Accounts, a standardized framework for the production of European Union statistics on economic activities. Utilizing various mathematical techniques and methods, the IO analysis shows adaptability as a tool of analysis. In comparison to alternative methods, one of the primary benefits of the IO method is its flexibility in incorporating aggregate data. This enables researchers and policymakers to gain a more comprehensive understanding of the interrelationships between different sectors of the economy as well as the effects of different policies on multiple sectors of the economy. This paper examines several studies by different authors related to IO analysis, which use official data from IO tables across various countries to analyze the economy of a country, region, and global impact. This paper evaluates the limitations of the application of the IO method in Albania, considering the techniques of constructing symmetrical IO tables and the types of analyses conducted through these data.